Tuberculosis of the foot and ankle in children - Maqungo, Sithombo (Department of Health and Rehabilitation Sciences, 2014)
The purpose of our retrospective study is to critically assess the long-term outcome of tuberculosis of the foot and ankle in children and to define an initial classification system that would relate to prognosis.